2012
DOI: 10.1007/s10646-012-0871-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological effects of ciprofloxacin on freshwater species: data integration and derivation of toxicity thresholds for risk assessment

Abstract: Although antibiotics have been increasingly used and detected in natural samples, their ecotoxicological effects on aquatic wildlife are not yet extensively studied. Considering the environmental threat posed by the biological activity of antibiotics it is quite relevant to assess the resulting impact, especially on sub-lethal endpoints. As such, this study evaluated the effects of ciprofloxacin on Pseudokirchneriella subcapitata and Lemna minor growth, on the survival and reproduction of Daphnia magna and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(38 citation statements)
references
References 46 publications
(67 reference statements)
0
28
0
Order By: Relevance
“…Thus, the grazer density used here (3 individuals mL −1 ) was similar to that used in previous studies on acute toxicity39. D. magna individuals were not fed during the test periods following previous studies394243.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the grazer density used here (3 individuals mL −1 ) was similar to that used in previous studies on acute toxicity39. D. magna individuals were not fed during the test periods following previous studies394243.…”
Section: Methodsmentioning
confidence: 99%
“…Toxiclogical effect information gained from current ecotoxicity testing which use racemic mixtures may therefore underestimate the risk actually posed in the environment. Findings from racemic toxicity testing have been used to recommend predicted effect/no effect concentrations (Ferrari et al, 2004;Quinn et al, 2008a;Martins et al, 2012) and can be seen as a precursor for environmental legislation and the proposal of quality standards. Although environmental legislation has safety buffers incorporated into their derivation, failure to recognise the enantiomeric distribution of chiral compounds in the environment and a lack of information on the toxicological differences between enantiomers is concerning.…”
Section: Chiralitymentioning
confidence: 99%
“…has been widely practiced, because of the higher sensitivity of algae compared to that of other microorganisms (bacteria, fungus, daphnids, and fish) toward the environmental stresses, which can induce the overaccumulation of reactive oxygen species in microalgae cells (Robinson et al, 2005;Isidori et al, 2005;Martins et al, 2012;Xiong et al, 2016Xiong et al, , 2017b. Risk assessment of 14 different antibiotics also showed that algae were more sensitive to the antibiotics than daphnids and fish (Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%